A Multi Case Study of Link and Match Program: Motorcycle Engineering and Business in VHS Tulungagung, Indonesia - Pamuji, Pipit Agung; Yoto, Yoto; Marsono, Marsono (Kayon Media, 2022)
Research on multi-case studies of link and match programs the motorcycle engineering and business industry class at SMK Tulungagung has been carried out. The research was conducted in three places including: SMK “SORE” Tulungagung and SMK Negeri 1 Rejotangan Tulungagung. The Honda industrial class program at SMK SORE Tulungagung has been going well, including the selection of an industrial class curriculum which involves the concept of link and match with industry, how the alignment of the industrial class curriculum is made. In addition, the learning process for the motorcycle engineering and business class at SMK Tulungagung has also been good, including the learning preparation process and the implementation of industrial class learning. What is no less important is the commitment of SMK which has a strategy to improve industrial class competence, namely increasing teacher competence and increasing student competence so that they are ready to go directly to industry.